2020
DOI: 10.3389/fpsyg.2019.03049
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chinese Reading Fluency by Verbal and Non-verbal Visual Attention Span Measures

Abstract: This study explored (1) the relationship between verbal and non-verbal visual attention span measures and (2) the relationship between visual attention span and reading fluency in traditional Chinese, among 101 university students in Hong Kong. The participants' visual attention span was assessed using verbal measures (i.e., a global report task and a partial report task) and non-verbal measures (i.e., visual 1-back task with Chinese characters and visual 1-back task with symbols). The results of the confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Group studies reported small to no correlations between performance on verbal STM and oral VAS tasks in dyslexic individuals (C. Chen, Schneps, Masyn, & Thomson, 2016; Cheng et al, 2021). Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007; Valdois et al, 2021; Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007; Bosse & Valdois, 2009; Chan & Yeung, 2020; C. Chen et al, 2016; Holmes & Dawson, 2014; Valdois et al, 2021; Zoubrinetzky et al, 2014). Although no study provided a direct comparison of performance in the whole and partial report tasks, similar levels were typically reported, or slightly higher performance in partial report (Bosse et al, 2007; Bosse & Valdois, 2009; Saksida et al, 2016; Zoubrinetzky et al, 2014, 2016).…”
Section: Is Vas Performance a Marker Of Verbal Processing?mentioning
confidence: 87%
See 2 more Smart Citations
“…Group studies reported small to no correlations between performance on verbal STM and oral VAS tasks in dyslexic individuals (C. Chen, Schneps, Masyn, & Thomson, 2016; Cheng et al, 2021). Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007; Valdois et al, 2021; Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007; Bosse & Valdois, 2009; Chan & Yeung, 2020; C. Chen et al, 2016; Holmes & Dawson, 2014; Valdois et al, 2021; Zoubrinetzky et al, 2014). Although no study provided a direct comparison of performance in the whole and partial report tasks, similar levels were typically reported, or slightly higher performance in partial report (Bosse et al, 2007; Bosse & Valdois, 2009; Saksida et al, 2016; Zoubrinetzky et al, 2014, 2016).…”
Section: Is Vas Performance a Marker Of Verbal Processing?mentioning
confidence: 87%
“…Group studies reported small to no correlations between performance on verbal STM and oral VAS tasks in dyslexic individuals (C. Chen, Schneps, Masyn, & Thomson, 2016;Cheng et al, 2021). Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007;Valdois et al, 2021;Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007;Bosse & Valdois, 2009;Chan & Yeung, 2020;C. Chen et al, 2016;Holmes & Dawson, 2014;Valdois et al, 2021;Zoubrinetzky et al, 2014).…”
Section: Behavioural Evidence From Alphanumeric Stringsmentioning
confidence: 97%
See 1 more Smart Citation
“…Typically, VA span is estimated through tasks of multi-letter or multi-digit oral report but the VA span is not specific to verbal tasks and alphanumeric material. It can be very similarly estimated using nonverbal tasks and non-verbal stimuli, like symbols or pseudo-letters (Chan & Yeung, 2020;Lobier et al, 2012). Performance on VA span tasks reflects the amount of visual attention capacity available for processing (Dubois et al, 2010;Lobier et al, 2013), which relates to the dorsal attention network (Lobier et al, 2014(Lobier et al, , 2012Reilhac et al, 2013;Valdois et al, 2019aValdois et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be the case. Indeed, there is growing evidence that visual attention is a concurrent and longitudinal predictor of word reading fluency (Bosse & Valdois, 2009;Chan & Yeung, 2020;Valdois et al, 2019;van den Boer & de Jong, 2018) and word spelling acquisition (Niolaki et al, 2020;Valdois et al, submitted;van den Boer et al, 2015) and that individuals with reduced visual attention capacity are slow readers and poor spellers (Bosse et al, 2007;Chen et al, 2019;Valdois et al, 2011;Valdois et al, 2021;Zoubrinetzky et al, 2014). Evidence that BRAID-Learn can account for the evolution of eye movement patterns when repeatedly confronted to the same input strings is further evidence in support of its theoretical assumptions.…”
Section: The Mechanisms Of Orthographic Learningmentioning
confidence: 95%